2018
DOI: 10.1007/s40263-018-0566-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Modifying Therapies for Relapsing–Remitting and Primary Progressive Multiple Sclerosis: A Cost-Utility Analysis

Abstract: Ocrelizumab would likely be cost effective as a first-line treatment for RRMS with a discounted price but was not cost effective for PPMS. Alemtuzumab dominated other options for second-line treatment of RRMS. Other DMTs were generally similar in terms of costs and health outcomes, providing health benefits compared to supportive care but with significant added costs. If drug prices were lowered, more DMTs could be cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…Os resultados obtidos nesta análise são qualitativamente similares aos descritos anteriormente, demonstrando a dominância de alentuzumabe comparado a natalizumabe em outras análises de custo-efetividade 25,26,27 . Apesar dos estudos terem analisado o uso de alentuzambe como tratamento em primeira linha, o natalizumabe também foi feito considerado nesta linha na análise.…”
Section: Discussionunclassified
“…Os resultados obtidos nesta análise são qualitativamente similares aos descritos anteriormente, demonstrando a dominância de alentuzumabe comparado a natalizumabe em outras análises de custo-efetividade 25,26,27 . Apesar dos estudos terem analisado o uso de alentuzambe como tratamento em primeira linha, o natalizumabe também foi feito considerado nesta linha na análise.…”
Section: Discussionunclassified
“…Three effects of shared decision making were assumed and modeled ( Figure 2 and further specified in the supplementary material): 1) shared decision making changes the DMD mix chosen, 2) shared decision making increases the proportion of optimally adherent patients, and 3) shared decision making increases persistence with the chosen treatment. Key assumptions for modeling shared decision making in comparison with usual care Figure 1 Health state transition model structure for multiple sclerosis course, adapted from Zimmermann et al 40 are presented in Table 1. Effect 1 was based on the fact that patients' preferences are elicited and included in the treatment choice during a shared decision making process, and these preferences might differ from physicians' preferences.…”
Section: Intervention Effectsmentioning
confidence: 99%
“…[15][16][17] No data were available for ocrelizumab and alemtuzumab. Discontinuation rates were therefore determined based on the rate of natalizumab, proportionately according to differences found in trial discontinuation rates between 28,40 Mortality risk within each health state was the same for RRMS and SPMS. Patients progressing to SPMS continued treatment with DMD.…”
Section: Intervention Effectsmentioning
confidence: 99%
“…Comparison of the DMT AOMS studies has inherent limitations; multiple comparisons have been reported including a value based comparison from the Institute for Clinical and Economic review, ICER, looking at the strength of the evidence, patient goals, and costs for each FDA approved DMT products [47]. A standardized ICER evaluation of all MS DMT concluded the newest FDA AOMS approved product, ocrelizumab dominating the other DMTs when cost was compared with supportive care for the AOMS patient, showing it as the best value in the US market or as cost effective as a first line treatment for RRMS [27]. There is no similar ICER evaluation for DMT use in POMS.…”
Section: Escalation Of Therapymentioning
confidence: 99%